2008
DOI: 10.1007/s00394-008-0707-x
|View full text |Cite
|
Sign up to set email alerts
|

Soy intake is related to a lower body mass index in adult women

Abstract: Background-Experimental and epidemiologic studies suggest that soy may promote weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…This finding is consistent with the reports of other epidemiological and experimental studies that suggested that soy intake may promote weight loss. (27)(28)(29) However, others have suggested that soy intake among certain groups of people may be an indicator of a healthy lifestyle, which contributes to weight loss, and that weight loss is not directly related to the properties of soy. (27) While our study did not further investigate the effect of quantity or frequency of soy consumption against obesity, it may be worthwhile for such a study to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the reports of other epidemiological and experimental studies that suggested that soy intake may promote weight loss. (27)(28)(29) However, others have suggested that soy intake among certain groups of people may be an indicator of a healthy lifestyle, which contributes to weight loss, and that weight loss is not directly related to the properties of soy. (27) While our study did not further investigate the effect of quantity or frequency of soy consumption against obesity, it may be worthwhile for such a study to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…fagifolia, Q. grandiflora and C. macrophyllum. Similarly to this work, there are reports in the literature that demonstrate that the use of plants may be related with reduced BMI. Maskarinec et al (2008) made this association with the use of soybean in adult women, and Ortega and co-workers et al (2006) reported this relationship with the consumption of vegetables and cereals.…”
Section: Biochemical Measurementsmentioning
confidence: 93%
“…There are plants that may contribute to the reduction of the body mass index (BMI) and show beneficial effects on the control of arterial blood pressure, such as Matico (Piper angustifolium R.), Guascas (Galinsoga parviflora), cocoa (Theobroma cacao), chickpea (Cicer arietinum L.), pea (Pisum sativum L.), fruits of Embelia ribes Burm, soy (Glycine max L.), and psyllium (Plantago psyllium L.) (RANILLA et al, 2010;SHIN et al, 2010;GRASSI et al, 2008;ALUKO, 2008;BHANDARI;ANSARI;ISLAM, 2008;MASKARINE et al, 2008;CICERO et al, 2007). In this study, after 30 days using quinoa cereal bar, 42.2% of the individuals showed reduced blood pressure and 40.7% showed reduced body weight.…”
Section: Biochemical Measurementsmentioning
confidence: 99%